Design of dispersant for highly concentrated one-dimensional Nb2Se9 inorganic molecular chains from bulk crystal - Chae, Sudong; Siddiqa, Akhtar J.; Oh, Seungbae; Kim, Bum Jun; Choi, Kyung Hwan; Yu, Hak Ki; Choi, Jae Young (Scientific Reports, 2019)
We determined the optimum dispersant to separate bulk Nb2Se9 material into 1D chain units. The Nb2Se9, which had a negative zeta potential (−43.3 mV), showed acidic characteristics and strongly bonded with the amine head of octadecyl amine through a charge transfer (from the amine to Se atoms) reaction. The steric hindrance of the octadecyl tail resulted in excellent dispersion of Nb2Se9 (down to nanometre-sized mono-chains).